Differential gene expression pattern in biopsies with renal allograft pyelonephritis and allograft rejection. Issue 9 (8th August 2016) - Oghumu, Steve; Nori, Uday; Bracewell, Anna; Zhang, Jianying; Bott, Cherri; Nadasdy, Gyongyi M.; Brodsky, Sergey V.; Pelletier, Ronald; Satoskar, Abhay R.; Nadasdy, Tibor; Satoskar, Anjali A.
Abstract: Differentiating acute pyelonephritis (APN) from acute rejection (AR) in renal allograft biopsies can sometimes be difficult because of overlapping clinical and histologic features, lack of positive urine cultures, and variable response to antibiotics. We wanted to study differential gene expression between AR and APN using biopsy tissue. Thirty‐three biopsies were analyzed using NanoString multiplex platform and PCR (6 transplant baseline biopsies, 8 AR, 15 APN [8 culture positive, 7 culture negative], and 4 native pyelonephritis [NP]). Additional 22 biopsies were tested by PCR to validate the results. CXCL9, CXCL10, CXCL11, and IDO1 were the top differentially expressed genes, upregulated in AR. Lactoferrin (LTF) and CXCL1 were higher in APN and NP. No statistically significant difference in transcript levels was seen between culture‐positive and culture‐negative APN biopsies. Comparing the overall mRNA signature using Ingenuity pathway analysis, interferon‐gamma emerged as the dominant upstream regulator in AR and allograft APN, but not in NP (which clustered separately). Our study suggests that chemokine pathways in graft APN may differ from NP and in fact resemble AR, due to a component of alloreactivity, resulting in variable response to antibiotic treatment. Therefore, cautious addition of steroids might help in resistant cases of graft APN.